2016
DOI: 10.5539/jmbr.v6n1p58
|View full text |Cite
|
Sign up to set email alerts
|

Effect of TiO2 Nanoparticles on Antioxidant Enzymes Activity and Biochemical Biomarkers in Pinto Bean (Phaseolus vulgaris L.)

Abstract: Tests were done on the effects of titanium dioxide spray on Pinto bean (Phaseolus vulgaris L. c.v 'c.o.s.16'). The study was conducted as a factorial experiment in a randomized complete block design with four replications for two years (2014 -2015). Treatments consisted of two factors; the first factor was stage of plant growth that spraying was applied (rapid vegetative growth, flowering and pod filling); and the second factor was that of different concentrations of titanium dioxide nanoparticles (TiO 2 ) tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Ebrahimi et al showed that nTiO 2 exposure could increase the activity of antioxidant enzymes and inhibit ROS in pinto bean leaves . Servin et al showed that inorganic soil exposed to 250–750 mg/kg nTiO 2 for 120 days can increase catalase activity, while inhibiting ascorbate peroxidase activity in cucumber plant leaves .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ebrahimi et al showed that nTiO 2 exposure could increase the activity of antioxidant enzymes and inhibit ROS in pinto bean leaves . Servin et al showed that inorganic soil exposed to 250–750 mg/kg nTiO 2 for 120 days can increase catalase activity, while inhibiting ascorbate peroxidase activity in cucumber plant leaves .…”
Section: Resultsmentioning
confidence: 99%
“…Ebrahimi et al showed that nTiO 2 exposure could increase the activity of antioxidant enzymes and inhibit ROS in pinto bean leaves. 57 Servin et al showed that inorganic soil exposed to 250−750 mg/kg nTiO 2 for 120 days can increase catalase activity, while inhibiting ascorbate peroxidase activity in cucumber plant leaves. 58 Laware and Raskar found that amylase, protease, catalase, and peroxidase activities increased when exposed to low concentrations of nTiO 2 (10−30 μg/mL) for 7 days but decreased in the presence of higher concentrations of nTiO 2 (50 μg/mL).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…NP treatments triggered the accumulation of reactive oxygen species, increased production of stress enzymes, lipid peroxidation that mediated oxidative stress in lentils ( Khan et al, 2019 ). Ebrahimi et al (2016) showed the installation of oxidative stress in Phaseolus vulgaris seedlings and disorder in antioxidant systems after treatment with TiO 2 NPs. In the same way, we showed that TiO 2 induced the antioxidant enzyme activities guaiacol peroxidase and catalase ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It is an important parameter to re ect the potential antioxidant capacity of organisms, and an important index of plant aging and resistance physiology. Thus, to assess the extent of damage to the plasma membrane system peroxidation and resistance of plants, the degree of membrane lipid peroxidation can be determined by measuring MDA content (La et al 2011;Ebrahimi et al 2016). In this study, compared with those in CK, Se treatment signi cantly increased SOD and POD activity of Feng Dan, and signi cantly reduced MDA content, maybe owing to Se directly participating in the enzymatic or non-enzymatic antioxidant process of organisms as a component of glutathione peroxidase (GSH-Px) system.…”
Section: Physiological and Biochemical Indexmentioning
confidence: 99%